1992
DOI: 10.1007/bf01270569
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine metabolism in ischemic and hypoxic hearts

Abstract: The rates of phosphatidylcholine biosynthesis in the isolated hamster hearts under ischemic and hypoxic conditions were examined. Global ischemia was produced by perfusion of the heart with a reduced flow, whereas hypoxia was produced by perfusion with a N2-saturated buffer. A 51% reduction in the biosynthesis of phosphatidylcholine was observed in the ischemic heart. The reduction was caused by a severe decrease in ATP level which resulted in a diminished conversion of choline into phosphocholine. A 22% reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Previously, study on isolated hamster hearts under ischemic and hypoxic conditions indicated that a 51% reduction in the biosynthesis of PC was observed in the ischemic heart and a 22% reduction in the biosynthetic rate of PC was also detected in the hypoxic heart. The lower level of circulating PC was thought to be the results of insufficient supply of adenosine triphosphate (ATP) and cytidine triphosphate (CTP) (23). Our results were in agreement with the above-mentioned reports in that at least one kind of downstream product of PC was in lower level in the SMI group (Fig.…”
Section: Figsupporting
confidence: 83%
“…Previously, study on isolated hamster hearts under ischemic and hypoxic conditions indicated that a 51% reduction in the biosynthesis of PC was observed in the ischemic heart and a 22% reduction in the biosynthetic rate of PC was also detected in the hypoxic heart. The lower level of circulating PC was thought to be the results of insufficient supply of adenosine triphosphate (ATP) and cytidine triphosphate (CTP) (23). Our results were in agreement with the above-mentioned reports in that at least one kind of downstream product of PC was in lower level in the SMI group (Fig.…”
Section: Figsupporting
confidence: 83%
“…Thus, this metabolite might be a very early marker of cell injury due to ischemia. Other changes include taurine and glutamine, which are amino acids known to be concentrated within cardiomyocytes (23). Alanine and glutamine follow opposite trends, as expected.…”
Section: Discussionmentioning
confidence: 55%
“…Changes in serum phospholipids have been associated with silent MIS (22). Ischemia may induce a 50% reduction in the biosynthesis of phosphatidylcholine (23). We also have found a rise in phosphoethanolamine, a constituent of the inner leaflet of the cell membrane, with little presence on the surface of normal viable cells (24).…”
Section: Discussionmentioning
confidence: 96%
“…The physiological responses mediated by hypoxia and Net, including cell migration, inflammation, wound healing, and angiogenesis, are similar. Moreover, all the identified target genes of Net are known to be regulated by hypoxia (3,11,12,21,28,34,38,39,48). In this study, we show that the transcription repressor function of Net is specifically downregulated in hypoxia.…”
mentioning
confidence: 50%